LEGAL EDUCATIONAL INSTITUTIONS IMPARTING QUALITY EDUCATION: A FUNDAMENTAL STEP TOWARDS ENSURING SUSTAINABLE DEVELOPMENT - Saini, Saloni; Jain, Mudit (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Sustainable Development has become the need of the hour. Today the human race is facing issues ranging from environmental hazards, socio-economic disparity, etc. All such issues become a stone on the road towards ensuring the holistic development of an individual. Since the future of any nation resides in the hands of the youth, it becomes imperative that youth be apprised not only of the issues, and their causes but also of the remedies for resolving such issues. Delivering quality education to the youth is perhaps one way to ensure sustainable development. Quality education makes an individual socially and morally responsible for his or her conduct in society. Institutions delivering legal education can play a role as catalysts towards ensuring sustainable development. Through their curriculum and other activities, they not only make young minds aware of the rights which include SDGs but also give them an opportunity to play a role towards ensuring achievement of such goals, like organizing conferences etc. on SDGs. However, in doing so, they have to face various barriers. Through this paper, the researchers would like to shed light on the role being played by legal educational institutions towards imparting quality education with reference to achieving sustainable development goals by adopting doctrinal research using primary and secondary sources like policies, journals etc.. The paper would further delve into the challenges being faced by such institutions in imparting such education and possible remedies for resolving such issues.